Pre-travel health care attendance among migrant travellers visiting friends and relatives (VFR): a 10-year retrospective analysis - Pietro Ferrara; Cristina Masuet-Aumatell; Josep Maria Ramon-Torrell (BMC, 2019)
Abstract Background Travellers visiting friends and relatives (VFR) define a specific population of travellers exposed to higher risks for health and safety than tourists. The aim of this study was to assess differentials in pre-travel health care in VFR travellers compared to other travellers. Methods A retrospective cohort study was performed including attendees of the Travel Medicine Clinic of the Hospital Universitari de Bellvitge, Barcelona, Spain, between January 2007 and December 2017. Results Over the 10-year period, 47,022 subjects presented to the travel clinic for pre-travel health care, 13.7% of whom were VFR travellers. These showed higher rates of vaccination against yellow fever and meningococcus, but lower rates for hepatitis A, hepatitis B, influenza, rabies, cholera, polio, typhoid IM vaccine and tetanus vaccine boosters. Regarding malaria prevention measures, results highlighted that VFR travellers, when compared with tourists, were more likely to be prescribed with chemoprophylaxis, particularly with mefloquine, than with atovaquone/proguanil. Conclusions Findings from this large-scale study indicated differences in vaccination rates and completion, as well as in chemoprophylaxis for malaria, between VFR and non-VFR travellers, fostering specific interventions for promoting adherence to pre-travel health advice among migrant travellers.